Can the Welfare State Justify Restrictive Asylum Policies? A Critical Approach - Sandelind, Clara (Ethical theory and moral practice, 2019)
Liberal egalitarians tend to be committed both to generous asylum policies and generous, universal welfare states. Yet there may be political, social and economic reasons why there is a conflict in realising both. Asylum seekers may create economic pressures to the welfare state, or undermine national solidarity supposedly necessary to support redistribution. In this paper, I discuss how political theorists should approach these empirical concerns. I take issue with the view that theorists can simply move between 'realism' and 'idealism' by accepting more or less of reality. Instead, political theorists should seek to offer a critical description of the conflict, which can reveal structures of power that ought to be subject to normative scrutiny. To this end, I discuss two accounts of how the welfare state may justify asylum restrictions in relation to the case of Sweden, a universal welfare state that has recently introduced restrictions on asylum to protect the welfare state. I argue along these accounts that the welfare state is both an important source of political and social order and a foundation of the personal moral experience. Yet a critical analysis also illustrates how these claims weaken as underlying methodological nationalism and bias towards existing power structures are brought to light. Asylum restrictions cannot be justified if they contribute to perpetuating these power structures, which cause some of the conflict with the welfare state in the first place.